Prevalence and associated factors of metabolic syndrome among patients with severe mental illness attending Amanuel Mental Specialized Hospital in Addis Ababa, Ethiopia: hospital-based cross-sectional study - Helena Getenet; Yeweyenhareg Feleke; Ruth Tsigebrhan; Tadesse Lejisa; Genet Ashebir (BMC Psychiatry)
Abstract Background Metabolic syndrome (MetS) is the leading cause of mortality and morbidity in patients with severe mental illness (SMI). The present study was designed to determine the prevalence and associated factors of MetS among people with SMI attending the Amanuel Mental Specialized Hospital in Addis Ababa, Ethiopia. Methods A hospital-based cross-sectional study was conducted among people with SMI attending the outpatient psychiatric department. Socio-demographic and other clinical data were collected using a structured questionnaire. A standardized chemistry analyzer measured lipid profiles and blood glucose levels at the Ethiopian Public Health Institute. Univariable and multivariable logistic regression analysis was conducted to examine the association of the outcome with clinical and socio-demographic variables. Results A total of 305 participants with SMI were recruited, 79% (n = 241) were male. The overall prevalence of MetS was 28.5% (n = 87), 31.5% (n = 63) among all the participants diagnosed with schizophrenia, and 25% (n = 13) among participants diagnosed with bipolar disorders. The most frequent metabolic abnormality was low high-density lipoprotein (HDL) 88.5% (n = 77). About 54% (n = 47) had abnormal waist circumference; 27.5% (n = 84) of the participants had a blood pressure of ≥ 130/85 mmHg; 4.6% (n = 14) had fasting blood glucose above 100 mg/dl; and 36.4% (n = 111) had triglyceride levels above 150 mg/dl. On multivariable analysis, increasing age (Adjusted odds ratio (aOR) = 1.12, 95% CI 1.08, 1.16) and having secondary education and above (aOR = 2.64, 95% CI 1.24, 5.50) compared to primary education, increasing duration of treatment (aOR = 1.11, 95% CI 1.03, 1.18) and alcohol use (aOR = 1.89, 95% CI 1.03, 3.47) were associated with MetS. 27.2% (n = 83) of the participants with SMI were overweight, and 4.6% (n = 14) had obesity. Increasing age (aOR = 1.11, 95% CI 1.05, 1.14), being female (aOR = 2.42, 95% CI 1.17, 5.01), smoking (aOR = 2.83, 95% CI 1.30, 6.15) and use of second-generation antipsychotics (aOR = 2.64, 95% CI 1.41, 4.94) were significantly associated with being overweight/obesity. Conclusions Individuals with SMI receiving care at a tertiary healthcare facility in Ethiopia exhibited a high prevalence of overweight/obesity and MetS. Therefore, health education and early screening for the components of MetS in this vulnerable population are recommended.